Addressing the Challenges of English Language Acquisition among Social Science Students in Resource Constrained Environments - syafriwana, syafiwana (Celebes Scholar pg, 2023)
A portrayal of pedagogical, motivational and resource dilemmas that hinder students in the acquisition of English language is discussed in this study. The study shows that students hardly bothered to learn English because they do not see any relevance of the language to their future professions. This is made worse by conventional theories which have insisted on mechanical language acquisition, memorization, drilling for grammar rules and structures without the development of communicative efficiency, and lack of instruction based on the individual learning abilities of the learners. Also, extreme scarcity of resources such as the English texts and technological facilities sufficiently affect opportunities of student language practice beyond the classroom. The study suggests that it is necessary to use more comprehensive approaches for overcoming these challenges such as changes is curricular in order to align it to English and students and their career needs, using more communicative and interactive methods, and supporting teachers for the implementation of differentiation. The study brings out important information that aligns well with other research done on language education especially in the developing countries so a policy maker or a practitioner you will find useful information to act on.